Proximate Composition and Nutritional Attributes of Ready-to-Cook Catfish Products - John M. Bland (MDPI AG, 2021)
To increase the demand for U.S. farm-raised catfish, five healthy, convenient ready-to-cook products were developed to expand consumers’ options beyond basic fresh or frozen fillets. Five new catfish products were produced, consisting of one hundred samples of each, including three size-types of Panko-breaded fish products (strips, center cuts of regular fillets, and center cuts from Delacata fillets) and two marinated products (sriracha and sesame-ginger). The breaded products were to be prepared by baking for convenience over traditional frying methods, while the marinated products were to be microwaved as healthy and convenient products. The nutrient content of the samples was analyzed, including protein, moisture, fat, fiber, ash, and carbohydrate, as well as minerals, amino acid, and fatty acid constituent content, with associated atherogenic index (AI) and thrombogenic index (TI), showing unique differences between the Panko-breaded and marinated products. In addition, a trend was observed showing an increase in moisture, protein, ash, and carbohydrate percentages, and a decrease in lipid content related to the volume-to-surface-area ratio, having the order of strips < standard fillets < Delacata fillets.